Iconography of The Adoration of the Shepherds in Late Medieval Italian Painting: A Bucolic Glance at the Existence of Pauper - Salvador González, José María (Eikón / Imago, 2012)
During the first twelve centuries of the Christian era, the artistic image of the Adoration of the Shepherds was overshadowed by that of the Adoration of the Magi. The latter was, in fact, identified, for the consumption of the ordinary Christian, as Epiphany par excellence, ie, the first public manifestation of Christ to mankind. Reported only by the Gospel of Luke, the story of the Adoration of the Shepherds was almost completely silenced by the apocryphal writings, as well as by the Church Fathers and medieval theologians, some of which only made ​​brief and sporadic references to this matter. However, in the context of several ascetic movements, promoted in Europe during the twelfth and thirteenth centuries by some lay people and monks in favor of evangelical poverty, harshly criticising the opulence often displayed by the clergy, the interest in representing the Adoration of the Shepherds increased with an oustanding success. By comparative analysis of a set of medieval Italian paintings that depict this iconographic subject, we propose in this paper two main objectives: first of all, to determine whether and to what extent these artistic images maintain a direct link with the ideas, beliefs, values ​​and behavior then in force in Italy; secondly, to highlight the substantial similarities and the obvious differences that the selected painters from Trecento and Quattrocento give to this topic, according to the profound change of doctrinal and ideological approach that can be seen between the two centuries.